INFLUENCE OF THE TRISTEZA VIRUS ON THE PHOSPHORUS (P32) DISTRIBUTION IN GALEGO LIME (Citrus aurantifolia CHRISTM) - Haag, H. P.; Silva, D. M.; Oliveira, J. C. de (REVISTA DE AGRICULTURA, 2015)
INFLUENCE OF THE TRISTEZA VIRUS ON THE PHOSPHORUS (P32) DISTRIBUTION IN GALEGO LIME (Citrus aurantifolia CHRISTM)